Steroid Receptor Signallings as Targets for Resveratrol Actions in Breast and Prostate Cancer - Francesca De Amicis (International Journal of Molecular Sciences, 2019)
Extensive research over the past 25 years in hormone-dependent cancers, such as breast cancer and prostate cancer, has identified the molecular mechanisms driven by steroid receptors, elucidating the interplay between genomic and non-genomic steroid receptors mechanism of action. Altogether, these mechanisms create the specific gene expression programs that contribute to endocrine therapy resistance and cancer progression. These findings, on the bidirectional molecular crosstalk between steroid and growth factor receptors pathways in endocrine resistance, suggest the use of multi-target inhibitors together with endocrine therapies, for treating resistant disease. In this review we will discuss the novel understanding on the chemopreventive and anti-cancer activities of Resveratrol (3,5,4′-trihydroxy-stilbene) (RSV), a phytoalexin found in grapes acting on a plethora of targets. We will highlight Resveratrol effect on steroid receptors signalling and its potential use in the treatment of hormone-dependent cancer. Understanding the molecular mechanisms by which the bioactive compound influences cancer cell behaviour, by interfering with steroid receptors functional activity, will help to advance the design of combination strategies to increase the rate of complete and durable clinical response in patients.